Triple Burden Index of Malnutrition - Umranikar, Anoushka; Joshi, Revati; Phadke, M (British Journal of Healthcare and Medical Research, 2025)
Malnutrition is a global public health priority. While described traditionally as undernutrition (with stunting, wasting, underweight); obesity & micronutrient deficiencyadd to the burden. While measuring this burden, a child may have more than one deficit and may get counted more than once thereby giving numbers greater than actual numbers. This fallacy is seen in many nutritional surveys giving incorrect estimates and results. We have devised a model, triple burden index which when used will give accurate estimates of all forms of malnutrition.